Georeferencing Libraries - Wijesundara, Chiranthi (My University, 2013)
GIS is a powerful technology that has the capability to provide solutions to an array of research problems in a variety of academic disciplines. The same set of data can be applied by researchers and scholars from different fields enabling crossfertilization of ideas among user groups. Geo Information for libraries may be a new concept to Sri Lankan society. Specially due to lack of technical knowledge and cost, most developing countries have ignored such aspects. However it is not a new concept to other countries world over. Though, with the rapid development in the society now it has become a reality in countries such as Sri Lanka as well. Since GIS is a tool which can be used to collect, maintain and present data this will be an ideal solution for library environment too. As the library exists to provide services to the users they can not operate in isolation from their market. The user population is constantly changing and making new demands for the library services. Equally the existing user population can always be better served than in the past. Both considerations imply a need for the information. Therefore, the present study is conducted to fill the existing gaps and to bridge the concept of GIS in Sri Lankan Libraries by providing useful outcomes to user community. Another aspect important for the networked information society of today is the highly intelligent use of the Internet and Web. It is well known that Linked Open Data (LOD) is an important aspect for libraries services. Bridging GIS and LOD for libraries is a crucial aspect to help users find information resources via library services wellconnected to the Internet. Also incorporating Metadata Harvesting techniques into the system will be another factor which will be considered in this study. The main objective of this study is to develop a model for the main Library of the University of Colombo to provide information for students, faculties, external users and other institutions to integrate and analyze data from many sources to develop new theories and knowledge. Moreover the same model can be used to Identifying library user requirements in GIS background. And this second objective can be used for decision making approaches by the top level personals in the library such as librarians. To achieve these objectives initially preliminary, data collection should be done to evaluate on existing user requirements and a questioner should be forwarded to ask views on the proposed approach from top level management of the library. In addition, details of other institutional repositories (Institutional repositories of other special libraries other than the University of Colombo) will be collected to develop a database by using ArcGIS software. After producing a database for both University of Colombo library and external institutional libraries, Maps and Models can be generated through specific data sets using special GIS software and these maps can categorized mainly in to User Category and Management Category. As the final step the prepared model can be linked to the University Web page for patrons with certain restrictions while other details are being used by the top level management of the library for decision making purposes.
Keywords: Geo Information, GIS, Linked Open Data (LOD), Metadata Harvesting